2011
DOI: 10.1155/2011/838951
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Sensitive Potassium Channel Currents in Eccentrically Hypertrophied Cardiac Myocytes of Volume-Overloaded Rats

Abstract: ATP-sensitive potassium channels (KATP) protect the myocardium from hypertrophy induced by pressure-overloading. In this study, we determined the effects of these channels in volume-overloading. We compared the effects of a KATP agonist and a KATP antagonist on sarcolemmal transmembrane current density (pA/pF) clamped at 20 mV increments of membrane potential from −80 to +40 mV in ventricular cardiac myocytes. The basal outward potassium pA/pF in myocytes of volume-overloaded animals was significantly smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Another study showed that the response of K ATP channel to its opener was markedly diminished for hypertensive rats [ 16 ]. Myocardial pathological hypertrophy not only reduces the responsiveness of K ATP channel to ATP but also makes K ATP channel fail to sensitize the opener cromakalim [ 17 , 18 ]. The impaired responsiveness of K ATP channel to the metabolic ligand or KCOs disrupts K ATP channel mediated cellular stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that the response of K ATP channel to its opener was markedly diminished for hypertensive rats [ 16 ]. Myocardial pathological hypertrophy not only reduces the responsiveness of K ATP channel to ATP but also makes K ATP channel fail to sensitize the opener cromakalim [ 17 , 18 ]. The impaired responsiveness of K ATP channel to the metabolic ligand or KCOs disrupts K ATP channel mediated cellular stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…ATP-sensitive K channels are essential for maintaining the cellular homeostasis against various metabolic stresses. Disease induced structural remodeling of cardiomyocytes may decrease or diminish the sensitivity of K ATP channel to ATP and/or its openers and alter this adaptive response to such stresses [ 15 18 ]. The dysfunctional K ATP channels in these conditions may fail to protect the myocardium from metabolic stresses or make the pharmacological therapy targeted to K ATP channels ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…Although Ito initiates repolarization, the delay in completing repolarization and prolonging depolarization is mainly a function of the phase 3 outwardly rectifying current, I K . We previously reported that downregulation of ATP-sensitive potassium channel current (I KATP ) is a characteristic of volume-overloaded, eccentrically hypertrophied adult rat cardiac myocytes which is thought to increase the duration of ventricular action potentials and increase inotropy of the myocytes [ 25 ]. The IGF-1 induced decrement in I K described in the present study might also contribute to prolonging ventricular action potentials.…”
Section: Discussionmentioning
confidence: 99%